The Importance of Public Policy for Regulating Post-Retirement Employment in Israel. - Cohen, Erez (Israel Studies Review)
The accelerated and consistent rise in life expectancy and the growing needs of elderly people who are required to support themselves for more years are leading to a conspicuous increase in the number of older workers who choose to remain in the labor market after reaching the official retirement age. The study indicates the distinct incompatibility between this policy and the needs of post-retirement age employees and proposes a list of changes aimed at adapting the policy to the current reality. The study stresses the significance of efficient public policy operating to regulate post-retirement employment for Israeli society in general and for older employees in particular. The research conclusions can contribute to shaping global public policy concerning the employment of older people.